PROGNOSES AND ANOMALY OF 24TH CYCLE OF SOLAR ACTIVITY - Lozitsky, V. G.; Efimenko, V. M. (Одеські астрономічні публікації, 2014)
Development of solar activity in 24th cycle has specific peculiarity – non-monotonous increasing of solar activity on grown phase which occurs for 1/3 number of all cycles. The modification of Waldmayer’s method was applied for forecasting 24th cycle which bases on a connection between maximum sunspot number and speed of increasing of activity on grown phase of cycle. If we compare 24th cycle with previous similar cycles Nos. 1, 5, 6, 9, 12, 15 and 16, we can conclude that this cycle will be weak, with maximum sunspot number Wmax (24) = 73 ± 10 in 2014–2015, most likely – in first half of 2014. Current cycle could be considered as anomaly by three criterions: a) sharp slowdown in growth after the 30th of the month cycle, b) two-humped peak cycle with a significant predominance of the second peak height and c) the emergence of a giant sunspot with a diameter of about 170 Mm.